2015
DOI: 10.7860/jcdr/2015/14850.6774
|View full text |Cite
|
Sign up to set email alerts
|

Colon-Cut-off-Sign in the CT- Scanogram – Evidence of Pancreatitis?

Abstract: A 53-year-old male patient was hospitalized with progressive upper abdominal pain. Physical examination findings: abdomen soft, no tenderness, no guarding, physiological peristaltic sounds. Laboratory results showed leukocytosis as well as elevated CRP, lipase and amylase. On the basis of the pronounced clinical symptoms, the patient was admitted to the department of internal medicine with the suspected diagnosis of a pancreatitis. As a result of pain exacerbation and an endoscopic examination in the area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this study, we also found some AP patients had dilatation of the gastrointestinal tract with gas. But it was a nonspecific finding and can occur in various diseases (41).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found some AP patients had dilatation of the gastrointestinal tract with gas. But it was a nonspecific finding and can occur in various diseases (41).…”
Section: Discussionmentioning
confidence: 99%